EFFECT OF TURNING PARAMETERS AND COOLANT USAGE ON TOOL WEAR IN LATHE PROCESS - REVIEW - Mardiah, Enok Mardiah; Hidayat, Imam (Jurnal Teknik Mesin (Journal Of Mechanical Engineering), 2025)
Turning products must have high quality. The quality of turning results can be affected by tool wear. Turning parameters and the use of coolant are the main factors that can control the level of wear, because they can control the temperature and cutting force during turning.  This study aims to examine the effect of turning parameters and coolant use on tool wear in the lathe process. The main parameters analysed include spindle rotation speed, depth of cut, and feed rate. In addition, the role of coolant as a coolant and lubricant is also studied in relation to controlling tool wear. The method used was a literature study. The results showed that all turning parameters have an influence on tool wear, with depth of cut as the most significant factor in increasing wear. High spindle speeds and large feeding motions also accelerate wear due to increased friction and temperature in the cutting zone. This means that the greater the parameter values used, the greater the tool wear. Where with a depth of cut of 0.05 mm causes tool wear of 0.094 mm, while with a depth of cut of 1.5 mm causes tool wear of 0.746 mm. With a spindle rotation speed of 185 rpm the tool wear is 2 mm, while with a spindle rotation speed of 2200 rpm the tool wear is 11.36 µm. With a feed motion of 0.05 mm/rev the tool wear was 0.094 mm, while with a feed motion of 1.5 mm/rev the tool wear was 0.746 mm. The use of coolant proved effective in lowering the cutting temperature, reducing friction, and extending tool life. The results of this study can serve as a practical reference in the selection of cutting parameters and cooling strategies to improve efficiency and tool life in the turning process.